1977
DOI: 10.1016/0010-0285(77)90008-1
|View full text |Cite
|
Sign up to set email alerts
|

In search of the M-Gram: The structure of organization in free recall

Abstract: This paper reviews three major classes of structural models of episodic and semantic memory which have been proposed to describe the organization of permanent memory. Although semantic memory workers have developed methods for obtaining representations of these models from empirical data, students of episodic memory generally have not. A method is presented for extracting representations of memory structure using output order information from a free recall learning task. It is shown that this method can be emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
40
0

Year Published

1978
1978
1991
1991

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 93 publications
0
40
0
Order By: Relevance
“…Friendly, 1977) showed that the subjective group structures for the JEP(H-16) and LUT(H-8) categories were the same hierarchical structures imposed by the experimenters. Further, a degree of structure had been imposed by the group on the DIB(N-16) and TOX(N-8) categories.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Friendly, 1977) showed that the subjective group structures for the JEP(H-16) and LUT(H-8) categories were the same hierarchical structures imposed by the experimenters. Further, a degree of structure had been imposed by the group on the DIB(N-16) and TOX(N-8) categories.…”
Section: Resultsmentioning
confidence: 81%
“…The training period of 12 weeks distinguished this study from that of Potts (1976) and Smith et al (1972), since their subjects studied the given information for only a few mintues. The subjective group structures for each category were examined by using a technique for inducing the organization of information in memory based on regularities in free recall, as proposed by Friendly (1977). The Friendly (1977) technique uses as the measure of similarity the average number of instances between each possible pair of instances in free recall lists of the category.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While subjective organization measures can indicate when an effect has occurred, they are of little use in determining how to produce a stronger one. One possibility would be to construct a spatial mapping (Friendly, 1977) of the subject's organizational structure from the data available from all previous trials. The materials could then be presented in a way that is maximally consistent with this structure.…”
Section: Resultsmentioning
confidence: 99%
“…One reason is that the use of trees in the representation and recognition of two-and three-dimensional patterns has received considerable attention in the automatic pattern recognition field (e.g., Pavlidis, 1977, Chapter 10), indicating their potential sufficiency as models. Another reason is that trees generally require less "memory capacity" than do networks to represent the same information (Friendly, 1977), although it might take more time to retrieve the information from a tree. A third reason is that it is usually better to resort to a complicated model only after a simpler version of the model has been shown to be inadequate.…”
mentioning
confidence: 99%